2152. Epidemiology and Clinical Outcomes of Contemporary, Third-Generation Left Ventricular Assist Device (LVAD) Infections. (26th November 2018) - Hershberger, Todd E; Kaye, Keith S; Chenoweth, Carol; Petty, Lindsay; Butler, Simona O; Clark, Angela M; Eschenauer, Gregory; Albin, Owen; Pagani, Francis D; Patel, Twisha S
Abstract: Background: Infection is a common complication following implantation of an LVAD. The purpose of this study was to characterize the epidemiology and clinical outcomes of infections in patients who received the HeartWare LVAD, a newer intrapericardial device. Methods: Adult patients with a HeartWare LVAD implanted between 2009 and 2017 at Michigan Medicine were screened for inclusion. LVAD-associated infection was defined using INTERMACS criteria. Patients were followed from device implantation to either infection, death, heart transplantation, device exchange, or last known follow-up to date. Exclusions included implantation of a right-sided VAD, alone or in combination with an LVAD. The primary outcomes were the incidence of LVAD-associated infections per 1, 000 device days and per 100 person-years. Results: Of the 183 patients included, 43 (23.5%) developed an LVAD-associated infection with incidence rates of 0.39 infections per 1, 000 device days and 14.3 infections per 100 patient years. The median time to infection was 305 days (IQR, 172–581). Staphylococcus spp. (26%) and Streptococcus spp. (20%) were the most common causative pathogens identified. The results of a univariate analysis for infection are shown in Figure 1. There were no statistically significant differences in all-cause mortality (40% vs. 17%, P = 0.08) and incidence of heart transplantation (19% vs. 34%, P = 0.09) between those with infection and those without infection; the number of hospital readmissions were more common in patients with infection (median, 4 vs. 2, P < 0.01). Conclusion: LVAD-associated infection remains a major complication among recipients of the HeartWare LVAD, with about one-quarter of patients developing infection over time despite improved device design. Infection contributes to the increased hospitalizations seen in this population. Disclosures: All authors: No reported disclosures.